Exploratory study on the dynamics of online responses to debunking messages about covid-19 in Singapore on Whatsapp - Chen, Xingyu (Nanyang Technological University, 2021)
The COVID-19 pandemic had spurred a concurrent outbreak of false information online. Debunking false information pertaining to a health crisis is critical as it can affect the public’s decisions to adhere to behaviours like mask-wearing. This exploratory study examined the effects of debunking messages on a COVID-19-related public chat on WhatsApp in Singapore.